Orbiting Jupiter - Schmidt, Gary D. (Houghton Mifflin Harcourt, 2017)
When Jack meets his new foster brother Joseph, he never imagines the bonds the two will form as they work together to find Joseph's daughter Jupiter. They will journey into a brotherhood that will rip open old wounds and require sacrifices from them both.